Single‐Crystal Germanium Core Optoelectronic Fibers. Issue 1 (19th September 2016) - Ji, Xiaoyu; Page, Ryan L.; Chaudhuri, Subhasis; Liu, Wenjun; Yu, Shih‐Ying; Mohney, Suzanne E.; Badding, John V.; Gopalan, Venkatraman
Abstract : Synthesis and fabrication of high‐quality, small‐core single‐crystal germanium fibers that are photosensitive at the near‐infrared and have low optical losses ≈1 dB cm −1 at 2 μm are reported. These fibers have potential applications in fiber‐based spectroscopic imaging, nonlinear optical devices, and photodetection at the telecommunication wavelengths.